2017
DOI: 10.1038/am.2016.210
|View full text |Cite
|
Sign up to set email alerts
|

Forced electrostriction by constraining polarization switching enhances the electromechanical strain properties of incipient piezoceramics

Abstract: Recently developed lead-free incipient piezoceramics are promising candidates for off-resonance actuator applications due to their exceptionally large electromechanical strains. Their commercialization currently faces three critical challenges: the high driving electric field required for delivering the potentially large strains; large strain hysteresis, which is inappropriate for precision devices; and relatively high temperature dependencies. We propose that instead of utilizing incipient piezoelectric strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…In 2007, Zhang et al reported a giant electric-field induced stain in ternary (Na 0.5 Bi 0.5 )TiO 3 -BaTiO 3 -(K 0.5 Na 0.5 )NbO 3 (NBT-BT-KNN) ceramics, [22] consequently leading to a rapid surge in the research of macrostrain enhancement and microstructure understanding in bismuthalkali-based systems. [25,[30][31][32][33][34] The origin of the giant strain has been determined to be a phase transition from unclear initial state into a ferroelectric tetragonal phase (P4mm), [32] but the ground state remains controversial concerning whether it is a nonergodic relaxor with an average cubic symmetry according to the dielectric dispersion or antiferroelectric state with extremely small distortion based on its double-hysteresis polarization-field loop. [9,16,30] Either way, long range order was perlocated with rhombohedral R3c and tetragonal P4bm symmetries, as evidenced by high-resolution transmission electron microscopy.…”
Section: Large Piezoelectricity In Ternary Lead-free Single Crystalsmentioning
confidence: 99%
“…In 2007, Zhang et al reported a giant electric-field induced stain in ternary (Na 0.5 Bi 0.5 )TiO 3 -BaTiO 3 -(K 0.5 Na 0.5 )NbO 3 (NBT-BT-KNN) ceramics, [22] consequently leading to a rapid surge in the research of macrostrain enhancement and microstructure understanding in bismuthalkali-based systems. [25,[30][31][32][33][34] The origin of the giant strain has been determined to be a phase transition from unclear initial state into a ferroelectric tetragonal phase (P4mm), [32] but the ground state remains controversial concerning whether it is a nonergodic relaxor with an average cubic symmetry according to the dielectric dispersion or antiferroelectric state with extremely small distortion based on its double-hysteresis polarization-field loop. [9,16,30] Either way, long range order was perlocated with rhombohedral R3c and tetragonal P4bm symmetries, as evidenced by high-resolution transmission electron microscopy.…”
Section: Large Piezoelectricity In Ternary Lead-free Single Crystalsmentioning
confidence: 99%
“…Apparently, in our BNT-BT-NN ceramics, the tailoring of microstructure (grain orientation) appears to have a positive effect in the production of high strain in terms of efficient domain switching from oriented grains. [34,38] Dielectric constant and loss of the random and textured ceramics depending on frequency (100 Hz-1 MHz) are compared in Figure 5a. The textured ceramics display nearly unchanged values of dielectric constant (≈1958 at 1 kHz) and loss (≈6% at 1 kHz) as compared to the random ones (≈1894 at 1 kHz and ≈5.2% at 1 kHz).…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, in our BNT–BT–NN ceramics, the tailoring of microstructure (grain orientation) appears to have a positive effect in the production of high strain in terms of efficient domain switching from oriented grains. [ 34,38 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations